Domestic Violence Against Women and Their Mental Health Status in a Colony in Delhi - Vachher, Alka S (Medknow Publications, 2010)
BACKGROUND: Violence against women is a major public health and human rights issue in the world today. This study was conducted to assess the consequences of domestic violence on the mental health of women of reproductive age group. MATERIALS AND METHODS: A community-based, cross-sectional study was conducted in Raj Nagar- I, urban locality in west Delhi near Palam. 350 women of 15-49 years age group residing in the community were selected by stratified random sampling. These women were administered an interview schedule adapted from WHO multi-country study on women’s health and domestic violence. They were assessed for the presence of domestic violence. Mental health status of these women was estimated by using self-reporting questionnaire 20. Data were analyzed using SPSS 12 software. The test applied was chi square test for proportion and binary logistic regression. RESULTS: 42.8% of the women reported one or the other types of violence. 34.9% of the women reported either physical or sexual violence ever in life. 29.1% of the women reported either physical or sexual violence in past 1 year (current violence). 12% of the women reported mental ill health. Women who had experienced domestic violence were more likely to report mental ill health status and suicidal tendencies as compared to women who had not experienced violence. CONCLUSIONS: Domestic violence is associated with mental ill health.